Urgensi Asbab An-Nuzul dalam Penafsiran Ayat-Ayat Al-Qur’an - Muhyidin Muhyidin; M. Fathor Rohman (Ummul Qura Jurnal Institut Pesantren Sunan Drajat (INSUD) Lamongan, 2022)
The Qur'an is a kalam of Allah that is revealed to the Prophet Muhammad gradually, and serves as a guide and guide for mankind. Although the Qur'an was revealed centuries ago, its editorship also uses Arabic, but its function and usefulness are universal, and valid throughout the ages until the apocalypse arrives. Therefore, there has been a lot of efforts by scholars in this field to formulate a way or method in order to understand the content of the verses of the Qur'an in question. Asbab An-Nuzul study is one of the businesses in question. The purpose of this paper is to understand in more detail Asbab An-Nuzul and how pentinya he is in understanding the verses of the Qur'an. The method used in this paper is library research, which is a type of research that focuses more on literature by analyzing the content of the existing literature and is descriptive-critical-historical related to Asbab An-Nuzul. The result is a fact that understanding asbab An-Nuzul will make it easier to understand the verse in question, to know in the context of who the verse is derived so as not to cause misunderstanding, also to facilitate memorization, and strengthen understanding in the hearts of people who know Asbab An-Nuzulnya. In conclusion, Asbab An-Nuzul is one way of understanding the verses of the Qur'an precisely according to the context.